Hubungan Tingkat Pengetahuan, Sikap Dan Dukungan Keluarga Terhadap Kepatuhan Diet Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Desitasari - -; Gamya Tri Utami; Misrawati - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine relationship between level of knowledge, attitude and family support with diet obedience of patients with chronic renal failure undergoing hemodialysis. Methodology on this research was descriptive correlatif with cross sectional. The study was conducted hemodialysis in Arifin Achmad Hospital Pekanbaru with 36 respondents. The sampling method was purpossive sampling . Measuring instrument used in the form of questionnaires that on validity and reliability and weigh scales. The analysis was used univariate and bivariate analysis by Chi Square test. The results showed that there was relathionship between level of knowledge and attitude with diet obedience of patients with chronic renal failure undergoing hemodialysis with p value (0,026) < α (0,05) and (0,039) < α (0,05). The results showed there was no relation between family support with adherence compliance patients chronic renal failure undergoing hemodialysis p value (0,243) > α (0,05). The results of this study recommends to health workers who work at hemodialysis ran provide health education about diet that the patient must through in to avoid weight gain, edema, and shortness of breath so it does not affect the loss of impact breaking in dietary compliance. Keywords:  Attitude, chronic renal, family support, hemodialysis, knowledge, obedience